On the reversibility of the α2/ωo phase transformation in a high Nb containing TiAl alloy during high temperature deformation. (10th December 2021) - Song, Lin; Appel, Fritz; Stark, Andreas; Lorenz, Uwe; He, Junyang; He, Zhanbing; Lin, Junpin; Zhang, Tiebang; Pyczak, Florian
Highlights: The reverse transformation ωo →α2 occurs during high-temperature deformation. The tilt angles between neighbouring α2 grains change from 56° to mostly 60° after annealing. A mixed structure of α2 +ωo phase replaced the original α2 laths in the annealed sample. Abstract: The transformations between the phases α2 (Ti3 Al) and ωo were investigated in a lamellar multiphase titanium aluminide alloy based on γ (TiAl). The paper complements an earlier investigation performed on the same material in which the importance of deformation-induced twin structures for the α2 →ωo transformation was demonstrated. The present study shows that the reverse transformation ωo →α2 can also occur during high-temperature deformation. The transformation is probably triggered by constraint stresses, which exist between the different constituents due to the crystalline mismatch. The combined operation of mechanical twinning of the α2 phase and the reversible transformation fully converts the α2 lamellae into a mixture of α2 and ωo . This conversion greatly reduces the mechanical anisotropy existing in former α2 lamellae. Regarding the technical use of the alloy, the stability of the converted structure with respect to further annealing was also examined. The reported processes occur at the nano-meter and sub nano-meter scale, thus, advanced characterization techniques were applied, such as high-resolution transmission electron microscopy (HRTEM) and atom probe tomography (APT). Graphical abstract: Image, graphical abstract